Drosophila melanogaster cloak their eggs with pheromones, which prevents cannibalism - Sunitha Narasimha; Konstantin O. Nagornov; Laure Menin; Antonio Mucciolo; Astrid Rohwedder; Bruno M. Humbel; Martin Stevens; Andreas S. Thum; Yury O. Tsybin; Roshan K. Vijendravarma (2019)
Oviparous animals across many taxa have evolved diverse strategies that deter egg predation, providing valuable tests of how natural selection mitigates direct fitness loss. Communal egg laying in nonsocial species minimizes egg predation. However, in cannibalistic species, this very behavior facilitates egg predation by conspecifics (cannibalism). Similarly, toxins and aposematic signaling that deter egg predators are often inefficient against resistant conspecifics. Egg cannibalism can be adaptive, wherein cannibals may benefit through reduced competition and added nutrition, but since it reduces Darwinian fitness, the evolution of anticannibalistic strategies is rife. However, such strategies are likely to be nontoxic because deploying toxins against related individuals would reduce inclusive fitness. Here, we report how D. melanogaster use specific hydrocarbons to chemically mask their eggs from cannibal larvae. Using an integrative approach combining behavioral, sensory, and mass spectrometry methods, we demonstrate that maternally provisioned pheromone 7,11-heptacosadiene (7,11-HD) in the eggshell's wax layer deters egg cannibalism. Furthermore, we show that 7,11-HD is nontoxic, can mask underlying substrates (for example, yeast) when coated upon them, and its detection requires pickpocket 23 (ppk23) gene function. Finally, using light and electron microscopy, we demonstrate how maternal pheromones leak-proof the egg, consequently concealing it from conspecific larvae. Our data suggest that semiochemicals possibly subserve in deceptive functions across taxa, especially when predators rely on chemical cues to forage, and stimulate further research on deceptive strategies mediated through nonvisual sensory modules. This study thus highlights how integrative approaches can illuminate our understanding on the adaptive significance of deceptive defenses and the mechanisms through which they operate.